Effect of Audit Quality and CEO Remuneration On Firm Performance: A Study on Pakistan Stock Exchange-Listed Non-Financial Firms - Muhammad Mehran; Faiza Zubair; Wafaq Ahmed (International Journal of Business and Economic Affairs, 2022)
This study analyzes the influence of audit quality and CEO remuneration on firm performance. The first independent variable is audit quality, and the indicators/variables used for audit quality are audit fees, audit committee size, and audit firm rotation. The second independent variable is CEO remuneration, which is considered as a sum of cash-based and non-cash-based (benefits) remuneration. At the same time, the dependent variables for this study are return on assets (ROA) and earnings per share (EPS), which are considered as measures/indicators for firm performance. The data is drawn from PSX-listed non-financial firms. The sample size consists of 70 firms for this study. However, the data does not incorporate the figures of financial firms as they were not relevant for this research. The data taken for analysis is secondary data, and the time frame is 10 years from 2010 to 2019, which is extracted from annual reports of PSX-listed firms. The reason for choosing this time frame is to analyze the most recent outcomes of the variables for this research. As the cross-sectional data is 70 firms, and the time frame is 10 years, so total observations for this research are 700, and panel data analysis has been applied. By analyzing the results of the fixed-effect model, it has been discovered that audit committee size is positively and significantly related to both ROA and EPS. However, the audit fee and audit rotation are insignificant to ROA and EPS. In addition, the CEO remuneration is positively and significantly related to ROA as a measure of firm performance. However, CEO remuneration is insignificantly related to EPS as a measure of firm performance.